Emission inventory of marine traffic for the Port of Rijeka - Radonja, Radoslav (Array, 2020)
The paper estimates the exhaust emissions of marine traffic in the Port of Rijeka based on the ship’s data obtained from the pilot company. The Port of Rijeka is the largest port in Croatia that includes several berthing locations with different terminals. The estimation is made for each of them respecting carbon dioxide (CO2), nitrogen oxides (NOx), sulphur oxides (SOx) and particulate matter (PM) as well as for the amount of total emissions for the area. The aim is to prepare basic records for estimation and further monitoring with respect to changes in the ongoing environmental regulation and restrictions. This paper will contribute to the overall national strategy of preparing shipping emission inventories for the Republic of Croatia. The estimation method is based on the bottom–up approach widely used in such research that starts with ship characteristics and activities when approaching the port.